An experimental device and experimental method for exploring a titanium alloy strengthening mechanism

CN117871811BActive Publication Date: 2026-10-09NANCHANG HANGKONG UNIVERSITY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311507694.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2026-10-09
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

但是在解耦出热效应和单独研究非热效应的影响中,该发明将铝合金板件的流动应力和变形阻力大幅降低并不能有助于研究

Benefits of technology

[0044] By employing liquid nitrogen cryogenic treatment, the influence of Joule heating in pulsed electric field assisted laser shock strengthening of titanium alloys was significantly reduced. Through experimental methods, different treatments were applied to four titanium alloy samples to decouple the thermal effects and separately study the influence of non-thermal effects, thereby exploring the dominant mechanisms of thermal and non-thermal effects in pulsed electric field assisted laser shock strengthening of titanium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117871811B_ABST
    Figure CN117871811B_ABST
Patent Text Reader

Abstract

The application discloses an experimental device and an experimental method for exploring a titanium alloy strengthening mechanism, and the experimental device comprises a pulse laser system component, a liquid nitrogen deep cooling system component and a clamping fixing system component; the pulse laser system component comprises a pulse laser, and is used for laser shock processing a titanium alloy sample; the liquid nitrogen deep cooling system component comprises a liquid nitrogen cooling plate, and is used for cooling the titanium alloy sample; the clamping fixing system component comprises a motion platform, a screw and a pressing plate; the liquid nitrogen cooling plate is first placed on the motion platform, then the titanium alloy sample is placed on the liquid nitrogen cooling plate, and then a protective layer material is adhered to a surface to be strengthened of the titanium alloy sample; subsequently, a constraint layer material is placed, and the titanium alloy sample is clamped by the screw and the pressing plate and fixed together with the liquid nitrogen cooling plate; and a computer is used for controlling the pulse laser and the motion platform. The application can analyze the difference of the titanium alloy sample strengthening mechanism under different strengthening treatment conditions, and explore the dominant mechanism of the thermal effect and the non-thermal effect of the pulse electric field assisted laser shock strengthening.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium alloy experiments, specifically to an experimental apparatus and method for investigating the strengthening mechanism of titanium alloys. Background Technology

[0002] Titanium alloys, due to their high specific strength, high fracture toughness, and excellent corrosion resistance, are widely used in key components of equipment in aviation, aerospace, and shipbuilding. For example, in the aviation field, titanium alloys are mainly used in the manufacture of fan blades and compressor blades inside aero engines. As is well known, titanium alloy blades operate under alternating loads and the coupled effects of high temperature and high pressure for extended periods, making their surfaces highly susceptible to varying degrees of damage. Furthermore, titanium alloys are extremely sensitive to damage and defects, leading to premature failure during use and severely impacting their service life and performance.

[0003] As an advanced surface strengthening technology, laser shock stabilization (LSS) can induce high-amplitude residual compressive stress on the material surface, while improving the material's microstructure, thereby significantly enhancing its service life and reliability. However, due to the poor elongation and formability of titanium alloys at room temperature, single LSS technology has significant limitations. Therefore, composite LSS technology has emerged. Pulsed electric field-assisted laser shock stabilization effectively improves the plastic deformation capacity of titanium alloys through the electroplastic effect of coupled pulsed electric fields, thereby obtaining a deeper surface strengthening layer and improved surface quality. The electroplastic effect is mainly a composite effect caused by non-thermal effects (pure electroplastic effect) and thermal effects (Joule heating effect). The pure electroplastic effect theory suggests that the pulsed current increases the activation energy of dislocation structures in the metal, accelerating the movement of dislocation structures and thus improving the metal's plasticity; the Joule heating effect theory suggests that the Joule heat generated when the current is applied softens the material, thereby improving the metal's plasticity. Currently, there is no unified understanding of the mechanisms of these two effects, mainly because it is difficult to decouple the thermal effect and study the influence of non-thermal effects separately.

[0004] A search revealed Chinese patent document CN115232924A, which discloses a device and method for laser shock forming assisted by high-pulse current and local cryogenicity. The device includes a laser shock forming system, a high-pulse current auxiliary system, a local cryogenic auxiliary system, a centering system, and a control system. The local cryogenic auxiliary system includes an insulated liquid chamber, liquid nitrogen, and an insulated rubber layer. The method utilizes the high strain rate effect of laser shock to improve grain refinement and generate residual compressive stress, thereby improving mechanical properties and fatigue resistance. The use of cryogenic-pulse current assisted coupling reduces deformation resistance, enhances the material's plasticity, and prevents brittle fracture of the formed part due to poor plasticity. The use of the insulated rubber layer effectively prevents the constraint layer from failing and reducing light transmittance in the cryogenic environment. Liquid nitrogen, as the force transmission medium, both homogenizes the shock wave pressure and achieves local cryogenic assisted forming, significantly saving liquid nitrogen. However, this device and method still struggle to decouple thermal effects and independently study the influence of non-thermal effects.

[0005] Chinese patent document CN115055811A discloses an electromagnetically assisted laser shock forming method and apparatus for aluminum alloys. According to the requirements of sheet bending, the surface of the aluminum alloy sheet is divided into a concave surface and a convex surface. An electric field is applied to both ends of the aluminum alloy sheet, and a magnetic field is applied to the other two ends. The direction of the electric field is perpendicular to the direction of the magnetic field. The magnetic force separates the positive and negative charges generated by the electric field, with positive charges distributed on the concave surface and negative charges distributed on the convex surface. An absorption layer is coated on the concave surface, and a continuously flowing constraint layer is provided on the concave surface. A pulsed laser shocks the concave surface to obtain an aluminum alloy sheet with curvature. This invention significantly reduces the flow stress and deformation resistance of the aluminum alloy sheet under the action of current and magnetic field, effectively suppressing the surface stress springback and significantly improving the limit forming size of the sheet. However, in decoupling thermal effects and studying the influence of non-thermal effects separately, this invention's significant reduction in the flow stress and deformation resistance of the aluminum alloy sheet does not necessarily contribute to the research. Summary of the Invention

[0006] In view of this, in order to solve the above-mentioned technical problems, the purpose of this invention is to propose an experimental device and method for exploring the strengthening mechanism of titanium alloys, which can decouple the thermal effect and study the influence of non-thermal effects separately, so as to analyze the influence mechanism of non-thermal effects and thermal effects.

[0007] The technical solution adopted is as follows:

[0008] An experimental apparatus for investigating the strengthening mechanism of titanium alloys according to the present invention includes:

[0009] A pulsed laser system component, comprising a pulsed laser, for laser shock strengthening of titanium alloy samples to obtain the required processing parameters for laser shock strengthening of titanium alloy samples.

[0010] A liquid nitrogen cryogenic system component, including a liquid nitrogen cooling plate, for cooling titanium alloy samples;

[0011] The clamping and fixing system components include a motion platform, screws and pressure plates. First, the liquid nitrogen cooling plate is placed on the motion platform, then the titanium alloy sample is placed on the liquid nitrogen cooling plate. Then, a protective layer material is adhered to the surface of the titanium alloy sample to be strengthened, followed by the placement of the constraint layer material. The titanium alloy sample is clamped and fixed together with the liquid nitrogen cooling plate using screws and pressure plates for subsequent laser shock strengthening processing.

[0012] A computer used to control pulsed lasers and motion platforms.

[0013] This includes calculating the control of the motion platform, for example, by controlling the drive motor installed on the motion platform. This drive motor is used to drive the motion platform.

[0014] Furthermore, the pulsed laser system components include a pulsed laser, a reflector, and a lens. The laser beam emitted by the pulsed laser is reflected by the reflector and then focused by the lens to obtain the required spot diameter, which is then used for laser shock strengthening of titanium alloy samples to obtain the processing parameters required for laser shock strengthening of titanium alloy samples.

[0015] Furthermore, the liquid nitrogen cryogenic system components include a liquid nitrogen storage tank, a shut-off valve, a liquid nitrogen pump, a pressure valve, liquid nitrogen pipelines, and a liquid nitrogen cooling plate. Liquid nitrogen in the liquid nitrogen storage tank flows through the liquid nitrogen pipeline, shut-off valve, and liquid nitrogen pump into the liquid nitrogen cooling plate to cool the titanium alloy sample, and is then discharged through the pressure valve.

[0016] An experimental method for investigating the strengthening mechanism of titanium alloys using the experimental apparatus described above, according to the present invention, includes the following steps:

[0017] S1. Make four identical titanium alloy samples, numbered 1#, 2#, 3#, and 4# respectively;

[0018] S2. First, take sample #1 and grind, polish, clean, and dry its surface to be strengthened. Then, adhere the protective layer material to the surface of the titanium alloy sample to be strengthened.

[0019] S3. Place the titanium alloy sample with black tape attached on a liquid nitrogen cooling plate, use quartz glass as the constraint layer material, place it on the surface of the titanium alloy sample to be strengthened, and then fix it with a pressure plate and screws.

[0020] S4. Open the laser control software on your computer and set the pulsed laser parameters, including pulse energy, frequency, and pulse width;

[0021] S5. Open the motion platform control software on the computer, move the motion platform and adjust the distance between the focusing lens and the titanium alloy sample surface to be strengthened to obtain the required spot diameter;

[0022] S6. Turn on the pulse power supply, adjust the pulse current frequency, pulse width and pulse power supply output current density, and then run the pulse power supply;

[0023] S7. Run the laser to perform impact strengthening on the titanium alloy sample. After each point impact is completed, the laser and pulse power supply need to be paused to replace the black tape and quartz glass. Then, move the motion platform a distance according to the set overlap rate, then run the pulse power supply, wait 1 minute and then run the laser to complete the impact of the next point.

[0024] S8. Repeat step S7 until the entire surface to be strengthened is strengthened;

[0025] S8. Take a No. 2 titanium alloy sample and repeat steps S2, S3, S4, S5, and S6 above respectively;

[0026] S9. Set the liquid nitrogen pump flow rate, adjust the liquid nitrogen outlet pressure value of the pressure valve, open the shut-off valve of the liquid nitrogen storage tank, and then run the liquid nitrogen pump to cool the titanium alloy sample for 1 minute;

[0027] S10. Run the laser to perform impact strengthening on the sample. Similarly, after each point impact is completed, the laser, pulse power supply and liquid nitrogen pump need to be paused to replace the black tape and quartz glass. Then, move the motion platform a distance according to the set overlap rate, then run the pulse power supply, wait for 1 minute and then run the liquid nitrogen pump, wait for another 1 minute and then run the laser to complete the impact of the next point.

[0028] S11. Repeat step S10 until the entire surface to be strengthened is strengthened;

[0029] S12. Take a No. 3 titanium alloy sample and repeat steps S2, S3, S4, and S5 above respectively;

[0030] S13. Set the liquid nitrogen pump flow rate, adjust the liquid nitrogen outlet pressure, open the shut-off valve of the liquid nitrogen tank, and then run the liquid nitrogen pump to cool the sample for 1 minute;

[0031] S14. Run the laser to perform impact strengthening on the sample. Similarly, after each point impact is completed, the laser and liquid nitrogen pump need to be paused to replace the black tape and quartz glass. Then, move the motion platform a distance according to the set overlap rate, run the liquid nitrogen pump, wait for 1 minute, and then run the laser to complete the impact of the next point.

[0032] S15. Repeat step S14 until the entire surface to be strengthened is strengthened;

[0033] S16. Take a No. 4 titanium alloy sample and repeat steps S2, S3, S4, S5, and S6 above respectively;

[0034] S17. After the pulse power supply runs for 1 minute, turn off the pulse power supply and immediately run the laser to perform impact strengthening on the sample. After each point impact is completed, the laser needs to be paused and the pulse power supply turned off to replace the black tape and quartz glass. Then, move the motion platform a certain distance according to the set overlap rate, and then turn on the pulse power supply. After the pulse power supply runs for 1 minute, turn off the pulse power supply and immediately run the laser to complete the impact of the next point.

[0035] S18. Repeat step S17 until the entire surface to be strengthened is strengthened;

[0036] S19. Phase, microstructure, residual stress and surface hardness of samples 1#, 2#, 3# and 4# after strengthening treatment were analyzed respectively. The differences and connections between the strengthened structure and properties of the four samples were compared. The differences in the strengthening mechanism of titanium alloy samples under different strengthening treatment conditions were analyzed in order to explore the dominant mechanism of thermal and non-thermal effects of pulsed electric field assisted laser shock strengthening.

[0037] Furthermore, in S1, the titanium alloy bar is cut into four titanium alloy samples of the same size using wire cutting.

[0038] Furthermore, in S2, black tape is selected as the protective layer material, and the black tape is adhered smoothly and without bubbles to the surface of the titanium alloy sample to be strengthened.

[0039] Furthermore, in S3, quartz glass is selected as the constraint layer material.

[0040] Furthermore, in S4, the parameters of the pulsed laser include a laser spot diameter of 3 mm, a wavelength of 1064 nm, a pulse width of 20 ns, a pulse energy of 1-15 J, and a frequency of 1-5 Hz.

[0041] Furthermore, in S6, the pulse power supply output current density is 0-100 A / mm. 2 For example, 10-90A / mm 2 The pulse current frequency is 10Hz-10kHz, and the pulse width is 10-1000μs.

[0042] Furthermore, in S9, the flow rate of the liquid nitrogen pump is 0-5 L / min, for example 1-4 L / min, and the load range of the pressure valve is 0-0.5 MPa, for example 0.1-0.4 MPa.

[0043] The beneficial effects of this invention are as follows:

[0044] By employing liquid nitrogen cryogenic treatment, the influence of Joule heating in pulsed electric field assisted laser shock strengthening of titanium alloys was significantly reduced. Through experimental methods, different treatments were applied to four titanium alloy samples to decouple the thermal effects and separately study the influence of non-thermal effects, thereby exploring the dominant mechanisms of thermal and non-thermal effects in pulsed electric field assisted laser shock strengthening of titanium alloys. Attached Figure Description

[0045] Figure 1 This is a schematic diagram of an experimental apparatus used to investigate the strengthening mechanism of titanium alloys.

[0046] Figure 2 for Figure 1 Schematic diagram of the cross-sectional structure along line AA in the middle.

[0047] In the diagram: 1-Pulsed laser; 2-Laser beam; 3-Reflector; 4-Lens; 5-Screw; 6-Pressure plate; 7-Liquid nitrogen pump; 8-Stop valve; 9-Liquid nitrogen storage tank; 10-Motion platform; 11-Pulsed power supply; 12-Pressure valve; 13-Liquid nitrogen cooling plate; 14-Titanium alloy sample; 15-Protective layer material; 16-Constraint layer material; 17-Computer; 18-Liquid nitrogen pipeline. Detailed Implementation

[0048] The present invention will be described in detail below through specific embodiments. However, the uses and purposes of these exemplary embodiments are only for illustrating the present invention and do not constitute any limitation on the actual protection scope of the present invention, nor are they intended to limit the protection scope of the present invention to these embodiments.

[0049] It should be noted that, for the sake of brevity, the titanium alloy sample can be simply referred to as the sample.

[0050] Example 1

[0051] Reference Figures 1-2 As shown, the present invention provides an experimental apparatus for investigating the strengthening mechanism of titanium alloys, specifically an experimental apparatus for investigating the strengthening mechanism of titanium alloys by pulsed electric field assisted laser shock. The apparatus includes a pulsed laser system component, a liquid nitrogen cryogenic system component, a clamping and fixing system component, and a computer 17. The pulsed laser system component is used to obtain the processing parameters required for laser shock strengthening. The liquid nitrogen cryogenic system component is used to cool the titanium alloy sample 14. The clamping and fixing system component is used to clamp, fix, and move the titanium alloy sample 14. The computer 17 is used to control the pulsed laser 1 and the motion platform 10.

[0052] In this embodiment, the pulsed laser system components include a pulsed laser 1, a reflector 3, and a lens 4. The laser beam 2 emitted by the pulsed laser 1 is reflected by the reflector 3 and then focused by the lens 4 to obtain the required spot diameter, which is then used for laser shock peening processing.

[0053] In this embodiment, the liquid nitrogen cryogenic system components include a liquid nitrogen tank 9, a shut-off valve 8, a liquid nitrogen pump 7, a pressure valve 12, a liquid nitrogen pipeline 18, and a liquid nitrogen cooling plate 13. Liquid nitrogen in the liquid nitrogen tank 9 flows through the liquid nitrogen pipeline 18, shut-off valve 8, and liquid nitrogen pump 7 into the liquid nitrogen cooling plate 13, cooling the titanium alloy sample 14 on the liquid nitrogen cooling plate, and then is discharged through the pressure valve 12. The liquid nitrogen pipeline is continuously arranged in an S-shape within the liquid nitrogen cooling plate.

[0054] In this embodiment, the clamping and fixing system components include a motion platform 10, a liquid nitrogen cooling plate 13, screws 5, and a pressure plate 6. First, the liquid nitrogen cooling plate 13 is placed on the motion platform 10, and then the titanium alloy sample 14 is placed on the liquid nitrogen cooling plate 13. Then, a protective layer material 15 is adhered to the surface of the titanium alloy sample 14 to be strengthened, and then a constraint layer material 16 is placed. The titanium alloy sample 14 is clamped and fixed together with the liquid nitrogen cooling plate 13 using screws 5 and pressure plate 6 for subsequent laser shock strengthening processing.

[0055] In this embodiment, both the pulsed laser 1 in the pulsed laser system assembly and the motion platform 10 in the clamping and fixing system assembly are controlled by the computer 17.

[0056] Example 2

[0057] An experimental method for investigating the strengthening mechanism of pulsed electric field assisted laser shock titanium alloys according to the present invention is carried out using an experimental apparatus for investigating the strengthening mechanism of pulsed electric field assisted laser shock titanium alloys as described in Example 1. The experimental method includes the following steps:

[0058] S1. Use wire cutting to cut the TC4 titanium alloy bar into four identical titanium alloy samples 14, numbered 1#, 2#, 3#, and 4# respectively; the dimensions of each titanium alloy square sample 14 are 10mm*10mm*5mm.

[0059] S2. First, take sample #1 and grind, polish, clean, and dry its surface to be strengthened. Use black tape as protective layer material 15 and adhere it to the surface of sample #1 to be strengthened. The black tape must be adhered smoothly and without bubbles. The thickness of the black tape used for protective layer material 15 is 0.15±0.02mm, and the thickness of the quartz glass used for constraint layer material 16 is 2mm.

[0060] S3. Place the titanium alloy square sample 1# with black tape attached on the liquid nitrogen cooling plate 13, select quartz glass as the constraint layer material 16, place it on the surface of sample 1# to be strengthened, and then fix it with screws 5 and pressure plate 6.

[0061] S4. Open the control software of laser 1 on computer 17 and set the pulse laser 1 parameters such as pulse energy, frequency and pulse width. In this embodiment, the pulse laser 1 parameters include a laser spot diameter of 3mm, a wavelength of 1064nm, a pulse width of 20ns, a pulse energy of 7J and a frequency of 1Hz.

[0062] S5. Open the control software of the motion platform 10 in the computer 17, move the motion platform 10 to adjust the distance between the focusing lens 4 and the surface of the sample to be strengthened in order to obtain the required spot diameter;

[0063] S6. Turn on the pulse power supply 11, adjust the pulse current frequency, pulse width, and pulse power supply output current density, and then run the pulse power supply 11; in this implementation case, the pulse power supply output current density is 15A / mm. 2 The frequency is 1kHz and the pulse width is 100μs.

[0064] S7. Run laser 1 to perform impact strengthening on sample #1. After each point of impact is completed, laser 1 and pulse power supply 11 need to be paused to replace the black tape and quartz glass. Then, move the motion platform 10 a certain distance according to the set overlap rate, and then run pulse power supply 11. After waiting for 1 minute, run laser 1 to complete the impact of the next point. In this embodiment, the laser spot overlap rate is 50% during the pulse electric field assisted laser impact strengthening process.

[0065] S8. Repeat step S7 until the entire surface to be strengthened is strengthened;

[0066] S8. Take sample #2 and repeat steps S2, S3, S4, S5, and S6 above respectively;

[0067] S9. Set the flow rate of liquid nitrogen pump 7, adjust the liquid nitrogen outlet pressure value of pressure valve, open the shut-off valve 8 of liquid nitrogen storage tank 9, and then run liquid nitrogen pump 7 to cool the sample for 1 minute; in this implementation case, the flow rate of liquid nitrogen pump 7 is 2L / min, and the load of pressure valve 12 is 0.2MPa.

[0068] S10. Run laser 1 to perform impact strengthening on sample #2. Similarly, after each point impact is completed, laser 1, pulse power supply 11 and liquid nitrogen pump 7 need to be paused to replace the black tape and quartz glass. Then, move the motion platform 10 a distance according to the set overlap rate, then run pulse power supply 11, wait 1 minute and then run liquid nitrogen pump 7, wait another 1 minute and then run laser 1 to complete the impact of the next point.

[0069] S11. Repeat step S10 until the entire surface to be strengthened is strengthened;

[0070] S12. Take sample #3 and repeat steps S2, S3, S4, and S5 above respectively;

[0071] S13. Set the flow rate of liquid nitrogen pump 7, adjust the liquid nitrogen outlet pressure, open the shut-off valve 8 of liquid nitrogen storage tank 9, and then run liquid nitrogen pump 7 to cool the sample for 1 minute;

[0072] S14. Run laser 1 to perform impact strengthening on sample #3. Similarly, after each point impact is completed, laser 1 and liquid nitrogen pump 7 need to be stopped to replace the black tape and quartz glass. Then, according to the set overlap rate, move the motion platform 10 a distance, then run liquid nitrogen pump 7, wait for 1 minute, then run laser 1 to complete the impact of the next point.

[0073] S15. Repeat step S14 until the entire surface to be strengthened is strengthened;

[0074] S16. Take sample #4 and repeat steps S2, S3, S4, S5, and S6 above respectively;

[0075] S17. After the pulse power supply 11 runs for 1 minute, turn off the pulse power supply 11 and immediately run the laser 1 to perform impact strengthening on sample #4. After each point impact is completed, the laser 1 needs to be paused and the pulse power supply 11 needs to be turned off to replace the black tape and quartz glass. Then, the motion platform 10 is moved a certain distance according to the set overlap rate. Then the pulse power supply 11 is turned on. After the pulse power supply 11 runs for 1 minute, turn off the pulse power supply 11 and immediately run the laser 1 to complete the impact of the next point.

[0076] S18. Repeat step S17 until the entire surface to be strengthened is strengthened;

[0077] S19. Phase, microstructure, residual stress and surface hardness of samples 1#, 2#, 3# and 4# after strengthening treatment were analyzed respectively. The differences and connections between the strengthened structure and properties of the four samples were compared. The differences in the strengthening mechanism of titanium alloy sample 14 under different strengthening treatment conditions were analyzed. The dominant mechanism of thermal and non-thermal effects of pulsed electric field assisted laser shock strengthening was explored.

[0078] For a better comparison of the steps performed on samples #1, #2, #3, and #4, please refer to Table 1:

[0079] Table 1

[0080] 1# S2, S3, S4, S5 S6, S7, S8 2# S2, S3, S4, S5 S6, S9, S10, S11 3# S2, S3, S4, S5 S13, S14, S15 4# S2, S3, S4, S5 S6, S17, S18, S19

[0081] By employing liquid nitrogen cryogenic treatment, the influence of Joule heating in pulsed electric field assisted laser shock strengthening of titanium alloys was significantly reduced. Through experimental methods, different treatments were applied to four titanium alloy samples to decouple the thermal effects and separately study the influence of non-thermal effects, thereby exploring the dominant mechanisms of thermal and non-thermal effects in pulsed electric field assisted laser shock strengthening of titanium alloys.

[0082] The detailed descriptions listed above are merely specific illustrations of feasible embodiments of the present invention, and are not intended to limit the scope of protection of the present invention. All equivalent embodiments or modifications made without departing from the spirit of the present invention should be included within the scope of protection of the present invention.

Claims

1. An experimental method for investigating the strengthening mechanism of titanium alloys using an experimental setup, characterized in that, The experimental apparatus includes: The pulsed laser system components include a pulsed laser, a reflector, and a lens. The laser beam emitted by the pulsed laser is reflected by the reflector and then focused by the lens to obtain the required spot diameter, which is then used for laser shock strengthening of titanium alloy samples to obtain the required processing parameters for laser shock strengthening of titanium alloy samples. The liquid nitrogen cryogenic system components include a liquid nitrogen storage tank, a shut-off valve, a liquid nitrogen pump, a pressure valve, liquid nitrogen pipelines, and a liquid nitrogen cooling plate. Liquid nitrogen in the liquid nitrogen storage tank flows through the liquid nitrogen pipeline, shut-off valve, and liquid nitrogen pump into the liquid nitrogen cooling plate to cool the titanium alloy sample, and is then discharged through the pressure valve. The clamping and fixing system components include a motion platform, screws and pressure plates. First, the liquid nitrogen cooling plate is placed on the motion platform, then the titanium alloy sample is placed on the liquid nitrogen cooling plate. Then, a protective layer material is adhered to the surface of the titanium alloy sample to be strengthened, followed by the placement of the constraint layer material. The titanium alloy sample is clamped and fixed together with the liquid nitrogen cooling plate using screws and pressure plates for subsequent laser shock strengthening processing. Computer, used to control pulsed lasers and motion platforms; and Pulse power supply; The experimental method includes the following steps: S1. Make four identical titanium alloy samples, numbered 1#, 2#, 3#, and 4# respectively; S2. First, take sample #1 and grind, polish, clean and dry its surface to be strengthened. Adhere the protective layer material to the surface of the titanium alloy sample to be strengthened, and use black tape as the protective layer material. S3. Place the titanium alloy sample with black tape attached on a liquid nitrogen cooling plate, use quartz glass as the constraint layer material, place it on the surface of the titanium alloy sample to be strengthened, and then fix it with a pressure plate and screws. S4. Open the pulsed laser control software on your computer and set the pulsed laser parameters, including pulse energy, frequency, and pulse width; S5. Open the motion platform control software on the computer, move the motion platform and adjust the distance between the focusing lens and the titanium alloy sample surface to be strengthened to obtain the required spot diameter; S6. Turn on the pulse power supply, adjust the pulse current frequency, pulse width and pulse power supply output current density, and then run the pulse power supply; S7. Run the pulsed laser to perform impact strengthening on the titanium alloy sample. After each point impact is completed, the pulsed laser and pulsed power supply need to be paused to replace the black tape and quartz glass. Then, move the motion platform a distance according to the set overlap rate, then run the pulsed power supply, wait for 1 minute, and then run the pulsed laser to complete the impact of the next point. S8. Repeat step S7 until the entire surface to be strengthened is strengthened; S9. Take a No. 2 titanium alloy sample and repeat steps S2, S3, S4, S5, and S6 above respectively; S10. Set the liquid nitrogen pump flow rate, adjust the liquid nitrogen outlet pressure value of the pressure valve, open the shut-off valve of the liquid nitrogen storage tank, and then run the liquid nitrogen pump to cool the titanium alloy sample for 1 minute. S11. Run the pulsed laser to perform impact strengthening on the sample. Similarly, after each point impact is completed, the pulsed laser, pulsed power supply and liquid nitrogen pump need to be paused to replace the black tape and quartz glass. Then, move the motion platform a distance according to the set overlap rate, then run the pulsed power supply, wait for 1 minute and then run the liquid nitrogen pump, wait for another 1 minute and then run the pulsed laser to complete the impact of the next point. S12. Repeat step S11 until the entire surface to be strengthened is strengthened; S13. Take a No. 3 titanium alloy sample and repeat steps S2, S3, S4, and S5 above respectively; S14. Set the liquid nitrogen pump flow rate, adjust the liquid nitrogen outlet pressure, open the shut-off valve of the liquid nitrogen tank, and then run the liquid nitrogen pump to cool the sample for 1 minute. S15. Run the pulsed laser to perform impact strengthening on the sample. Similarly, after each point impact is completed, the pulsed laser and liquid nitrogen pump need to be paused to replace the black tape and quartz glass. Then, move the motion platform a distance according to the set overlap rate, then run the liquid nitrogen pump, wait for 1 minute, and then run the pulsed laser to complete the impact of the next point. S16. Repeat step S15 until the entire surface to be strengthened is strengthened; S17. Take a No. 4 titanium alloy sample and repeat steps S2, S3, S4, S5, and S6 above respectively; S18. After the pulse power supply runs for 1 minute, turn off the pulse power supply and immediately run the pulse laser to perform impact strengthening on the sample. After each point impact is completed, the pulse laser needs to be paused and the pulse power supply turned off to replace the black tape and quartz glass. Then, move the motion platform a certain distance according to the set overlap rate, and then turn on the pulse power supply. After the pulse power supply runs for 1 minute, turn off the pulse power supply and immediately run the pulse laser to complete the impact of the next point. S19. Repeat step S18 until the entire surface to be strengthened is strengthened; S20. Phase, microstructure, residual stress and surface hardness of samples 1#, 2#, 3# and 4# after strengthening treatment were analyzed respectively. The differences and connections between the strengthened structure and properties of the four samples were compared. The differences in the strengthening mechanism of titanium alloy samples under different strengthening treatment conditions were analyzed in order to explore the dominant mechanism of thermal and non-thermal effects of pulsed electric field assisted laser shock strengthening.

2. The experimental method according to claim 1, characterized in that, In S1, wire cutting is used to cut the titanium alloy bar into four titanium alloy samples of the same size.

3. The experimental method according to claim 1, characterized in that, In S2, black tape is applied smoothly and without bubbles to the surface of the titanium alloy sample to be strengthened.

4. The experimental method according to claim 1, characterized in that, In S4, the pulsed laser parameters include a laser spot diameter of 3 mm, a wavelength of 1064 nm, a pulse width of 20 ns, a pulse energy of 1-15 J, and a frequency of 1-5 Hz.

5. The experimental method according to claim 1, characterized in that, In S6, the pulse power supply output current density is 0-100 A / mm 2 The pulse current frequency is 10 Hz-10 kHz, and the pulse width is 10-1000 μs.

6. The experimental method according to claim 1, characterized in that, In S10, the flow rate of the liquid nitrogen pump is 0-5 L / min, and the load range of the pressure valve is 0-0.5 MPa.

Citation Information

Patent Citations

  • Electromagnetic-assisted aluminum alloy laser shock forming method and device

    CN115055811A

  • Strong pulse current and local cryogenic assisted laser shock forming device and method

    CN115232924A

  • Laser impact micro forming device and micro forming process thereof of medical titanium alloy plate

    CN104772569A

  • Copious cooling work table, copious cooling laser shock peening experiment system and control method thereof

    CN106319176A

  • Experiment method for adjusting local sate of titanium alloy Alpha / Beta phase interface

    CN110426410A